2002
DOI: 10.1179/026708302225007736
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on statistics of extremes for three-dimensional distribution of non-metallic inclusions

Abstract: A wide range of studies have shown that the lower bound of fatigue properties of high strength steels is determined by the maximum size of non-metallic inclusions that are present in a component. The maximum size of inclusions in a given component or material volume can be reasonably estimated using the statistics of extremes. However, as long as the estimation is based on microscope inspections of two-dimensional (2D) surfaces, there will be errors and uncertainties in estimating the maximum particle in a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…As was recently shown in the problem of inclusions in steel, this method could be extended to the estimation of three-dimensional sizes of large pores in specified volumes of material. 36,40,43,44 Finally, different types of porosity could be taken into account by using new approaches, based on mixed model or competing risk model. [43][44][45] Conclusions In this paper, two statistical methods, based on the statistics of extremes theory, were studied to predict the maximum pore size in laser welded joints longer than the inspection domain.…”
Section: Suggestions For Further Studymentioning
confidence: 99%
“…As was recently shown in the problem of inclusions in steel, this method could be extended to the estimation of three-dimensional sizes of large pores in specified volumes of material. 36,40,43,44 Finally, different types of porosity could be taken into account by using new approaches, based on mixed model or competing risk model. [43][44][45] Conclusions In this paper, two statistical methods, based on the statistics of extremes theory, were studied to predict the maximum pore size in laser welded joints longer than the inspection domain.…”
Section: Suggestions For Further Studymentioning
confidence: 99%
“…Furthermore, they concluded that the largest microstructural defect determines the fatigue limit. Based on the experimental works [9][10][11][12][13][14], it is possible to extract the following key points: (a) the investigated martensitic steels SAE 4150 and SAE 4140 show fatigue crack nucleation on free surfaces as well as at oxidic and sulfidic inclusions with varying sizes, shapes and orientations to loading axis, (b) the MnS inclusions reveal a complex delamination behavior in case of transversal loading and (c) the lower bound of fatigue properties is controlled by the maximum size of non-metallic inclusions within the high stressed volumes [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The size of frontal inclusions in a specimen was determined; they initiated a fatigue crack. It was demonstrated in [9,22] that the presence of large non-metallic inclusions which form during steel deoxidation results in a sudden drop in fatigue strength. Such inclusions often have a crucial effect on the mechanism of initiation of a fatigue crack, especially in the area close to infinite fatigue strength or with a high-frequency load [8,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration the results of fatigue tests on 16MnCr5 steel after LPC treatment and the main cause of the loss of cohesion under cycle loading, i.e. non-metallic inclusions based on calcium and aluminum presented in papers [8,9,19,22], the numerical model in ANSYS 18.0 environment was created. Original FEM model was complemented with a couple of possible positions of non-metallic inclusion in the technological surface layer.Based on observations of yield stress distribution around the inclusion, the possible crack initiation sited were sought after.…”
Section: Introductionmentioning
confidence: 99%